Pengaruh Entrepreneurial Self Efficacy, Social Identity, Networking dan Spiritualitas terhadap Entrepreneurial Intention - Fitri Rima Hidayati; Abdul Mujib (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Entrepreneurial intention is the awareness of individuals that they intend to organize new business ventures and plan to do so in the future. This research aims to see whether entrepreneurial self efficacy, social identity, networking and spirituality together influence entrepreneurial intention. The sample in this research amounted to entrepreneurs who participated in the YukBisnis seminar held in Jakarta and Lampung. Sampling used in this research using non-probability sampling techniques by convenience sampling technique. This research method uses quantitative methods. The validity of the measuring instruments in this research was tested by Confirmatory Factor Analysis (CFA). Data analysis uses multiple regression analysis (multiple regression). The results showed that there was an influence of entrepreneurial self-efficacy variables (searching, planning, marshaling, implementing people, implementing financial), social identity (Darwinian founders: basic social motivation, basic for self-evaluation, frame of reference. Communitarian founders: basic social motivation, basic for self-evaluation, frame of reference Missionary founders: basic social motivation, basic for self-evaluation, frame of reference), networking (content of changed networking), spirituality (meaning, value, transcendence, connecting, becoming ) towards entrepreneurial intention, namely with a large contribution of 30.3%. The results of the test of the proportion of variance from each independent variable indicate that entrepreneurial self efficacy (planning, searching), social identity (Darwinian founders: basic social motivation, besic for self evaluation, missionary founders: basic for self evaluation), networking (networking support ), spirituality (meaning, value) has a significant influence on entrepreneurial intention.